Evaluation of Students' Achievement in the Development of Innovative Learning Tools for PPG Computer Engineering and Informatics Students Using the Rasch Model - Manggopa, Hiskia; Batmetan, Johan Reimon (JR Education, 2024)
This research aims to measure students' performance from the Teacher Professional Education Program (PPG) in Category 1 Batch 2 Computer and Informatics Engineering at Manado State University in 2023 using the Rasch Model. The Rasch Model was chosen as a measurement method because it can provide a more accurate picture of individual student abilities, as well as identify the level of difficulty and differentiating power of each evaluation item. The research method involves collecting student performance data through various evaluation instruments, such as written exams, projects, and practical assignments. The collected data is then analyzed using the Rasch Model to evaluate the quality of the measurements and understand the extent to which the evaluation instrument can describe students' true abilities. The research results are expected to provide in-depth insight into the abilities of PPG students in Category 1 Batch 2 Computer Engineering and Informatics, as well as provide recommendations for improvements to the evaluation instruments used. Applying the Rasch Model in measuring student performance is expected to increase objectivity and accuracy in assessing students' abilities, which in turn can support improving the quality of education at Manado State University.